1993
DOI: 10.1090/s0273-0979-1993-00427-0
|View full text |Cite
|
Sign up to set email alerts
|

A new measure of growth for countable-dimensional algebras

Abstract: Abstract.A new dimension function on countable-dimensional algebras (over a field) is described. Its dimension values for finitely generated algebras exactly fill the unit interval [0,1 ]. Since the free algebra on two generators turns out to have dimension 0 (although conceivably some Noetherian algebras might have positive dimension!), this dimension function promises to distinguish among algebras of infinite GK-dimension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The growth algebras G(r), introduced by Hannah and O'Meara [10,11,13] in the early 1990's, were originally defined over a field, but the same definitions still apply when the matrix entries are from any ring R. The ring of all ω × ω matrices over R which are simultaneously row-finite and column-finite is denoted by B(R). For a matrix x ∈ B(R), a growth curve for x is any function g :…”
Section: Translation Algebras and Exchange Rings 2069mentioning
confidence: 99%
See 2 more Smart Citations
“…The growth algebras G(r), introduced by Hannah and O'Meara [10,11,13] in the early 1990's, were originally defined over a field, but the same definitions still apply when the matrix entries are from any ring R. The ring of all ω × ω matrices over R which are simultaneously row-finite and column-finite is denoted by B(R). For a matrix x ∈ B(R), a growth curve for x is any function g :…”
Section: Translation Algebras and Exchange Rings 2069mentioning
confidence: 99%
“…This appears to be new even in the case where R is a field. In that setting, the papers [10,11,13] referred to the corresponding algebra of constant bandwidth matrices as the growth algebra G(0), because it was the first of a whole spectrum of growth algebras G(r), for r in the unit interval [0,1], that were used to define the bandwidth dimension of an arbitrary countable-dimensional algebra. For 0 < r ≤ 1, the G(r) are still translation algebras relative to a suitable pseudo-metric, and an easy extension (Theorem 3.1) of our main result shows that all the G(r) are exchange algebras.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [HO1,HO2,O], Hannah and O'Meara introduced and studied a new notion of growth for algebras. This notion does not involve the growth of an algebra in terms of generators.…”
Section: §1 Introductionmentioning
confidence: 99%
“…Recently it was shown that any countably generated algebra over a field K can be embedded in RCFM(K) [3,Proposition 2.1]. This result, in turn, was used to define a new dimension function on such algebras [5]. The ring RCFM(R) has arisen in the context of Morita equivalence [4], exchange rings [1,7], and Baer rings [2].…”
Section: Introductionmentioning
confidence: 99%